Selective binding of benzoquinone with a Pt-II-cyclophane constructed on the skeleton of N,N `-bis(salicylidene)-p-phenylenediamine: synthesis and spectroscopic studies - Kumari, Niraj; Prajapati, Rishikesh; Dixit, Mudit; Mishra, Lallan (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2009)
The Schiff base NN'-bis(salicylidene)-p-phenylenediamine has been complexed with Pt(en)Cl-2 and the resulting Pt-II-cyclophane, [Pt(en)L](2)center dot 4PF(6), reacted with phenol, resorcinol, hydroquinone or benzoquinone in DMSO solution. Their binding has been monitored by the variation in the corresponding UV-visible and emission spectral patterns. The binding properties are compared with the earlier reported Zn-II-cyclophane [Zn(bpy)L](2) (bpy = 2,2'-bipyridine). A few solid adducts of phenol and benzoquinone with the Pt-II-cyclophane complex and hydroquinone as well as that of resorcinol with the Zn-cyclophane have also been synthesized and characterized.
Keywords: Coordination chemistry; Cyclophanes; Metallocyclophanes; platinum; Schiff bases

High charge carrier mobility in two dimensional indium (iii) isophthalic acid based frameworks - Panda, Tamas; Banerjee, Rahul (Proceedings of the National Academy of Sciences India Section A-Physical Sciences, 2014)
The effect of dimensionality (1D to 2D) on charge carrier mobility have been studied thoroughly on three In(III)-isophthalate based MOFs [In-IA-1D, In-IA-2D-1 and -2]. In-IA-1D possess 1D nanotubular architecture with [(CH3)(2)NH2](+). In-IA-2D-1 have 2D layers containing only [(CH3)(2)NH2](+) cations. Whereas, In-IA-2D-2 have [(CH3)(2)NH2](+) cations as well as solvent DMF molecule inside the crystal structure. Due to presence of the pi-pi stacking arrangement among the phenyl rings of IA moieties facilitates the high charge carrier mobility (4.6 x 10(-3) cm(2) V-1 s(-1) at V-G = -40 V) in In-IA-2D-2. However, In-IA-1D and In-IA-2D-1 does not show any charge carrier mobility due to absence of pi-pi stacking arrangement.
Keywords: Charge carrier mobility; Coordination chemistry; metal organic framework; pi-pi stacking

Supported MoOx and WOx solid acids for biomass valorization: interplay of coordination chemistry, acidity, and catalysis - Sudarsanam, Putla; Gupta, Navneet Kumar; Mallesham, Baithy; Singh, Nittan; Kalbande, Pavan Narayan; Reddy, Benjaram M.; Sels, Bert F. (ACS Catalysis, 2021)
Supported molybdenum oxide (MoOx) and tungsten oxide (WOx) materials are a vital class of solid acid catalysts for the chemical industry because of their nontoxic nature, strong acidity, remarkable stability in water, hydrogen, and oxygen atmospheres, and excellent reusability performance. These fascinating solid acids play a pivotal role in developing sustainable catalytic routes for renewable biomass processing to produce value-added fuels, chemicals, and platform molecules. The coordination chemistry of MoOx and WOx on the support materials (oxides, carbons, or zeolites) controls their acidic strength, active site accessibility, and catalytic activity. Hence, significant efforts have been made toward optimizing the conditions used for catalyst synthesis and biomass processing to tune the coordination chemistry of MoOx and WOx with the substrate molecules and, thus, their acid-activity/selectivity performance. This Review provides a comprehensive overview of supported MoOx and WOx solid acids for biomass valorization. The importance of the biomass and the role of solid acids for biomass valorization were emphasized, followed by a brief discussion of supported MoOx and WO(x )solid acids. Afterward, the interplay of coordination chemistry, acidic strength, and catalytic activity of supported MoOx and WOx solid acids was discussed. Finally, their catalytic applications for the valorization of several biomass substrates and their derivatives were summarized. This Review will provide valuable insights for developing advanced supported WOx and MoOx solid acids for catalytic biomass valorization and other challenging acid-catalyzed processes.
Keywords: Acidity; biomass valorization; catalysis; Coordination chemistry; molybdenum oxide; tungsten oxide